Educação no campo: Mobral no meio rural de Uberlândia/MG (1970-1985) - Oliveira, Letícia Borges de (2011)
The Brazilian movement toward literacy Movimento Brasileiro de Alfabetização (Mobral) started with the military coup d état in 1964, having as its main characteristic the quantitative expansion of the education of young adults and adults, being in fact more like a mass process of education than its democratization, that s why the results were really timid and doubtful because it prioritized the adult education. Historically, the campaigns to teach people to read and write promoted by the federal government emerged in Brazil with the proposals to reduce the high rates of illiteracy that started bothering the different levels of government, since the thirties, when the processes of industrialization and urbanization started in a high rate. However, the education continued being offered in an unequal way to the different social classes, such policy reached mostly the economically impaired groups, specially the people that couldn t frequent school at the appropriate age. Mobral, as a public policy to teach people to read and write, is also included in this context. At the beginning of the 1970s, it got to its apogee with the promise of getting rid of illiteracy in ten years, president Médici considered illiteracy a national shame . The aim was to achieve one million two thousand students throughout the country with the measures of the Integrated Program of Education of Mobral. In this period, Minas Gerais was highlighted as the first state in student number and cities that were included in this campaign. This research investigates the process of implantation and development of the Movimento Brasileiro de Alfabetização (Mobral) in the rural area of the city of Uberlândia/MG. The secular clipping contemplated the years of 1970 the 1985, period of validity of the program. Our specific objectives were: understand the process of implantation and development of the Mobral in the rural area; b) to analyze the specifics of this educational experience in the rural context of Uberlândia; c) contribute to the discussion of the history of regional education and, thus, promote the necessary link between the local and the national study. The documentary research was carried out from reading reports in newspaper the Reporter and Correio of Uberlândia , deposited in the Municipal Public Archive. Along the way, also analyze the characteristics and contents of textbooks used in the campaign as the Book of Reading, the express Cartilha of the Mobral and the historical registers in books and photographs which were carefully guarded by some former-pupils and former-teachers. In this process, also resorted to interviews given by those subjects who experienced the reality of Mobral in the field, including the former-coordinator of the program in the city Olga Lara Cardoso.